Pain Associated with Endometriosis. A Review of Quality of Life. Psychological Aspects, Career Development, Sexual Health, and Intimate Partner Relationships - Marlena Zubiak; Martyna Byrska; Hanna Barska-Kobylińska; Sara Langner; Ewa Katarzyna Malaka; Marta Janura; Jagoda Elias; Wiktor Biesiada; Sara Szydłowska; Krzysztof Błaszków (Quality in Sport)
Introduction: Endometriosis is a chronic estrogen-dependent inflammatory disease characterized by the presence of tissue resembling the endometrium outside the uterine cavity. It affects approximately 10% of women of reproductive age. The main symptoms include severe pain, reduced fertility, and sexual dysfunction. Treatment includes pharmacotherapy and surgical interventions, depending on the severity of symptoms, the location of lesions, and their extent.